Thematic Handouts Teaching Materials Based on Picture Stories Improving Reading Interest and Learning Outcomes of Fourth Grade Elementary School Students - Maulida, Ikrima; Suma, Ketut; Sudiana, Nyoman (Universitas Pendidikan Ganesha, 2022)
Students' interest in reading is still low and there is still a lack of teaching materials that can increase interest in reading and student learning outcomes, especially when learning online. This study aims to produce a product in the form of thematic handout teaching materials based on picture stories on 8 sub-theme 3 themes for fourth-grade elementary school. This research is development research using the Borg and Gall model. The trial subjects in this study were 36 students of class IV. The data collection method used a questionnaire to obtain validity and practicality as well as reading interest and learning outcomes tests for effectiveness. Data collection instruments in the questionnaire consisted of content/material expert instruments, media expert instruments, design expert instruments, practitioner practicality sheets, student response questionnaires, reading interest questionnaires, and learning outcomes tests. The data analysis used is quantitative and qualitative. The results showed that the validity of the thematic handout teaching materials based on picture stories through content/material experts, media experts, and design experts was stated to be very good and feasible to use. The practicality of thematic handouts based on illustrated stories by teachers and students are 100% and 91.3% with very practical categories. The results of the effectiveness test obtained showed an average result of 0.76 for reading interest and 0.72 for learning outcomes in the high effectiveness category. So, it can be concluded that the thematic handout teaching materials based on picture stories are suitable for use in the learning process.